Endometrial condition when using the contraceptives (according to cytology smears) - N G Baeva; Yu A Filyaeva (IP Berlin A.V., 2014)
In this paper, a comparative assessment of the endometrium in patients using levonorgestrel induced intrauterine system (IUS) Mirena and copper IUDs is presented, on the basis of cytology smears performed after removal of the IUD.The study included women who have already given birth, and those who never have, and that makes it more meaningful in terms of assessing the various conditions of endometrium as a factor in reproductive health.The return of fertility (for a year's period) in women who choose to perform the reproductive function has been analyzed as well.